Comparative Analyses of Maliki and Hanbali Thought on Waqf Istibdāl - Lapatantja, Nanda Arisqa; Bakry, Muammar (Universitas Islam Negeri Alauddin Makassar, 2021)
This article aims to describe and Analyze dissent from Maliki and Hanbali on the practice of istibdāl endowments and endowment empowerment adopted by Act No. 41 of 2004. Type this research is the library which is based on data management obtained from several kinds of literature. This research approach uses a normative approacpp. This study indicates that there are differences in the views of the Maliki School and the Hambali School related to the practice of istibdal waqf. In this paper, the opinion of the Maliki School distinguishes two categories in the practice of istibdal waqf, namely movable waqf property and immovable waqf property. Movable waqf property is allowed to practice istibdal waqf because the movable waqf property can no longer be used. At the same time, the waqf property that does not move is not allowed to practice istibdal except with emergencies such as the expansion of masjid, cemeteries, and public roads, unlike the case with the Hambali School, which does not distinguish movable waqf property or immovable waqf property. This school prioritizes the benefits of the waqf. If the community can no longer use it, it is permissible to practice istibdal following its terms and conditions. Moreover, the ability to practice istibdal waqf in the Hambali School is quite relevant to conditions in Indonesia, following Law Number 41 of 2004 concerning waqf, which both aim to optimize the benefits of waqf and empowering waqf assets